A importância da quantificação da reserva cognitiva - Sobral, M.; Pestana, M.H.; Paúl, C. (Revista Portugesa de Enfermagem de Saúde Mental (RPESM), 2014)
BACKGROUND: Cognitive Reserve (CR) is a hypothetical construct used to obtain information about cognitive aging, which describes the capacity of the adult brain to cope with the effects of neurodegenerative processes and it is conceived as a dynamic construction. AIMS: Compare the performance of a group of patients with Alzheimer's disease (AD), and a group of healthy elderly people (control) on CR Questionnaire (CRQ); Cognitive and functional assessment of patients with AD and controls with different levels of CR; To know the predictors of CR. METHODS: Functional and neuropsychological abilities of 50 outpatients with probable AD diagnosis and of 30 healthy elderly were evaluated. All participants answered the CRQ. RESULTS: Analysis of variance (ANOVA) showed no significant differences on scores between CRQ and the control group and between CRQ and the group of patients with AD. Logistic regression results for both groups indicated that the CRQ scores were significantly influenced by education (p<0.000) and occupation (p< 0.000). CONCLUSION: All participants with higher levels of CR obtained higher scores on cognitive tests comparatively to older people with lower levels of CR. The CRQ is a useful tool to quantify the level of CR in people with healthy elderly and patients with AD instrument. The education and occupation throughout life are predictive of levels of CR. Keywords: Cognitive Reserve; Questionnaires; Alzheimer's disease